2019
DOI: 10.1155/2019/8691294
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 Expression Increases in the Aorta and Plasma of Patients with Acute Aortic Dissection

Abstract: Background. Interleukin- (IL-) 18 is a proinflammatory cytokine related to cardiovascular diseases, including hypertension and atherosclerosis. This study is aimed at determining whether IL-18 is related to aortic dissection (AD) and identifying the underlying mechanisms. Methods. IL-18 expression in human aorta samples from AD (n=8) and non-AD (NAD, n=7) patients was measured. In addition, the IL-18, IL-6, interferon- (IFN-) γ, and IL-18-binding protein (IL-18BP) concentrations in plasma samples collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
(39 reference statements)
0
10
0
1
Order By: Relevance
“…Previous studies have shown that IL-6 signaling is mediated by macrophage activation in Ang IIinduced vascular disease (Schuett et al, 2009), and that the IL-6-STAT3 model pathway regulates the downstream Th7-IL-17 axis and upregulates monocyte macrophage activity (Ju et al, 2013). IL-18 may promote M1 macrophage differentiation and increase macrophage-induced apoptosis of SMCs (Hu et al, 2019). Taken together, it appears that macrophages secrete ILs to promote local inflammation of the aortic wall, while receiving regulatory signals from ILs to further expand the inflammatory response, for the ultimate promotion of AD.…”
Section: Effects Of Ils On the Aortic Wallmentioning
confidence: 99%
“…Previous studies have shown that IL-6 signaling is mediated by macrophage activation in Ang IIinduced vascular disease (Schuett et al, 2009), and that the IL-6-STAT3 model pathway regulates the downstream Th7-IL-17 axis and upregulates monocyte macrophage activity (Ju et al, 2013). IL-18 may promote M1 macrophage differentiation and increase macrophage-induced apoptosis of SMCs (Hu et al, 2019). Taken together, it appears that macrophages secrete ILs to promote local inflammation of the aortic wall, while receiving regulatory signals from ILs to further expand the inflammatory response, for the ultimate promotion of AD.…”
Section: Effects Of Ils On the Aortic Wallmentioning
confidence: 99%
“…14 Development of a mouse model that demonstrated unregulated TGF-b resulted from the altered matrix in fibrillin-1 deficiency, paved the way for research into the immunological basis of aortic diseases including AAS (Table 2). 10,11,14,[16][17][18][19][20][21][22][23][24][25] Immunohistochemical studies have examined the role of inflammation in AAS in detail, particularly for AD. One study tested patients' serum monocyte level and found it to be higher in those with AD.…”
Section: Immunological Basis Of Aasmentioning
confidence: 99%
“…Interleukin-18 18 Produced by immune cells such as T lymphocytes, macrophages, and vascular smooth muscle cells.…”
Section: Seen In a Mouse Model Of Aortic Dissectionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The histopathology of aortic aneurysm and dissection involves loss of small muscle cells and elastin fibers resulting in medial degeneration, and aortic wall softening. 4,5 High aortic wall tension due to acute or chronic pressure load enhances aneurysm formation and the extent of dissection. 2 The severity of the aortic wall degeneration may be associated with the propagation of aortic dissection.…”
Section: Introductionmentioning
confidence: 99%